Non-standard language structures on Facebook: an analysis of the influence of topics and purposes - Usop, Nuruljannah; Abdul Ghani, Rozina (IIUM Press, International Islamic University Malaysia, 2017)
This book examines the purposes of various topics posted on Facebook and explores whether topics lead to the employment of non-standard language. The use of non-standard language features include morphological, lexical, orthographical, and typographical deviations. This book employed convenience sampling as 60 Malaysian participants from the researcher’s Facebook contacts were involved. Herring’s (2007) situations classification was utilized to explore the communicative purposes and topics. An adopted and adapted version of Volckaert-Legrier, Bernicot, and Bert-Erboul’s (2009) types of deviation taxonomy and Herring’s (2010) e-grammar classification were selected to examine the non-standard and deviant linguistic features. The findings reveal that sharing information and self-expression are the main communicative purposes. Nonetheless, a number of status updates has more than one communicative purpose. The results also suggest that topics do, to a certain extent, significantly affect the use of non-standard language. The communicative purposes seem to have a remarkable influence on the participants’ language use as well. The findings are in line with Herring’s (2007) situational factors in which both topics and communicative purposes shape language use in the online milieu. These findings may broaden one’s understanding of how language works in the online discourse.